Correlation between band alignment and enhanced photocatalysis: a case study with anatase/TiO2(B) nanotube heterojunction1. Issue 29 (7th August 2015) - Wang, Changhua; Zhang, Xintong; Wei, Yongan; Kong, Lina; Chang, Feng; Zheng, Han; Wu, Liangzhuan; Zhi, Jinfang; Liu, Yichun
<x xml:space="preserve">Abstract</x> A type II band alignment and migration of electrons from anatase to TiO2(B) result in enhanced photocatalysis.